EFEKTIVITAS DISIPLIN PEGAWAI DI SEKERTARIAT DAERAH KOTA PEKANBARU - Mutiara Ramadhona; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Government civil servant discipline are the acceptance of the government civil servant to stick on the rules and avoiding the prohibition that is regulated in the laws, rules from ministry of law, and human rights. Researcher found there is lot of interesting cases that in reality there is still found employees breaking the rules like not staying at workplace at the working time, coming late, and others. That thing are really interesting to be research about. This research is purposely to know how the disciplinary of the employee at regional secretariat.This research Mahmudi (2005:92) theory effectiveness related with the relationship between the expected result with the actual results achieved. Effetiveness is the outcome versus output.The result show that there are factors that affect disciplinary effectivity of the employee at the regional secretariat are the value of compensation given, the leadership of the company leader and are there any real rules that can be used as a guide by the employee.Keywords: effectiveness, working discipline, employee performance